(untitled) (Fiep Bulletin - online, 2013)
In the collective sporting games (JDC), specifically Basketball there are various technical elements that demand of the player the motor skills to play it. It is also known that for each action involving the execution of the correct technique of an element, a motor skill is needed, and the characteristics of a sporting motor skill reflects in the final result. This characteristic can be determined by the speediness in its execution, or, for the agility and speed of swapping of the player in a specific space. It is understood that the development of the agility as well as the speed are essential factors, before initiating in Basketball, reason for which the modality will demand of the future athlete fast movements in different rhythms. For a long period as trainer in the basketball modality, it was noticed fragility of the beginners in regards to the agility and to the speed at the moment of the initiation. Then, we tried to develop activities that grant motion experiences to the beginners, so that the same ones can supply such needs with regard to the two motion requirements. The study was characterized as experimental, being the sample consisted of pupils between 11 and 13 years old from a public school in Presidente Prudente - SP, that are part of the project Ball in the Basket. The pupils had been submitted to activities for the development of the agility and the speed, together with the initiation of the technical basis. The data of the before and after-tests were submitted to statistical treatment using the test of comparison for coupled data, finding the differences between the obtained observations and comparing them with the critical value based on the table t- Student with the level of significance á (á=0.05). The analyzed data revealed that it had significant statistical difference between them. It was concluded that the development of the agility and the speed are essential factors, before and during the initiation at Basketball, offering therefore, considerable increase in the individual technique for the future athlete.